Effect of mangrove crab (Sesarma huzardi) extract on haematology and lung histology in swiss mice infected with Bordetella pertussis - Enyi, Ikpechi Ovundah; Isirima, Joshua Charles (Faculty of Natural and Applied Sciences Journal of Scientific Innovations, 2023)
Pertussis or whooping cough is a severe human respiratory tract disease caused by Bordetella pertussis, a known worldwide pathogen that affects infants, children and adults. This study is aimed at investigating the changes in haematological parameters and histopathological changes of the lungs associated with Bordetella pertussis infection in swiss mice and to evaluate the potential of Sesarma huzardi extract to reverse these adverse changes concerning erythromycin treatment. The animals were divided into five groups: group 1 was normal to control, group 2 was infected with Bordetella pertussis without treatment (negative control), groups 3 and 4 were Bordetella pertussis infected and treated with 300mg/kg and 600mg/kg of the extract respectively and group 5 was infected and treated with 4000mg/70kg of erythromycin in divided doses. The animals were inoculated with a single infectious dose of Bordetella pertussis bacteria and were consequently treated with the graded doses of the extract and erythromycin for eighteen days after the animals were confirmed infected. The mice were euthanized using diethyl ether anaesthesia and blood samples were taken for haematological investigation and lung tissue was harvested and processed for histological examination. The result shows that inoculation of mice with an infective dose of B. pertussis reveals a gradual decrease in PCV, Hemoglobin, Platelet, RBC and Eosinophil levels when compared to the normal control but these alterations were reversed when treated with Sesarma huzardi extract and there was a steady increase in PCV, Hemoglobin, platelet and RBC as the day progresses. The result showed that Sesarma huzardi extract reversed the changes in the haematological parameters and pathological changes in the lungs of mice infected with Bordetella pertussis in a dose and time-dependent manner which suggests curative potentials of Sesarma huzardi extract against B. pertussis